Devising a method for the active coordination of video cameras in optical navigation based on the multi-agent approach - Burlachenko, Ivan; Zhuravska, Iryna; Musiyenko, Maksym (Eastern-European Journal of Enterprise Technologies, 2017)
Here we present results of research into multi-agent approach to solving the problem of constructing a wireless Ad Hoc network to transmit video stream during optical navigation. When obtaining data from video cameras in real time, there is a problem of realization of effective coordination of video data. To improve the algorithms of capturing an object, it is necessary to improve the architecture of devices that utilize network metadata for the analysis of scenes from video surveillance. As a result of exploring the ways of solving the specified problems, we proposed a method for active coordination of video cameras based on the multi-agent approach (MAC-on-MAA). The application of this method increases efficiency of network cameras through their reconfiguration. We examined the problem of determining an adequate level of illuminance normalization of a video frame based on analysis of the modules throughput of multi-agent system for encoding transmitted video data. It was revealed that the time of analysis of video stream from a network decreases when ignoring the decoding of certain domains of graphic elements in the received video frames. The devised MAC-on-MAA method allows effective updating of routing tables in the reactive protocol AODV. We obtained analytic expressions for the assessment of quantitative characteristics of energy consumption by mobile agents. Protection of communication channels of video surveillance network is improved through the integration of steganocontainers in the free bits of RGB characteristics of video frames pixels.